Answers

  • qais
  • Content Quality
2016-01-20T12:00:46+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let roots be α and β
A/q
α = 6β 
now, if α and β are roots then equation will be (x -α)(x -β) =0
 (x -α)(x -β) =0
⇒ x² - (α+β)x + αβ =0 
now putting α = 6β ,
⇒x² - (6β +β)x + 6β×β =0
⇒x² - 7βx +6β² =0 
now comparing with  kx² -14x +8 =0
7β =14/k
⇒β =2/k
⇒β² = 4/k²_______(1)
and 6β² =8/k
⇒β² =4/3k_______(2)
equating (1) and (2), we get,
4/k² = 4/3k
k =3

7 3 7